if a cos^3 theta + 3 a sin^2 theta cos theta = m and a sin^3 theta + 3 a cos ^2 theta = nprove that (m+n)^2/3 + (m - n)^ 2/3 = 2a ^ 2/3

Printable View

- Jun 10th 2010, 10:45 PMsaha.subhamprove that
if a cos^3 theta + 3 a sin^2 theta cos theta = m and a sin^3 theta + 3 a cos ^2 theta = nprove that (m+n)^2/3 + (m - n)^ 2/3 = 2a ^ 2/3

- Jun 10th 2010, 10:55 PMpickslides
Start with

$\displaystyle \frac{(m+n)^2}{3} + \frac{(m - n)^ 2}{3}$ or is it $\displaystyle (m+n)^{2/3} + (m - n)^ {2/3}$ ??

make the relevant substitutions for m and n from above then expand and simplify until you get the RHS